The Influence Of Market Orientation And Product Innovation On Marketing Performance Through Competitive Advantage In Tiktok Shop Content Creators - Sarah Safira; I Made Sukresna (UNIVED Press, 2024)
Good marketing means sales will increase. The aim of this research is to find out whether market orientation and product innovation influence marketing performance, and to find out whether competitive advantage is able to mediate market orientation and product innovation on marketing performance.The population in this study are TikTok shop content creators who are members of official groups. The total sample was 115 respondents using accidental sampling technique. Data collection techniques use questionnaire and observation methods. The data analysis method uses multiple linear regression with a path analysis approach and the SPSS program.The research results show that market orientation variables and product innovation have an influence on marketing performance, then competitive advantage also has a positive and significant influence on marketing performance. The results of the indirect influence test also show that competitive advantage is able to mediate the relationship between market orientation and product innovation on marketing performance.Implementation of market orientation strategies and product innovation influence the marketing performance of TikTok Shop content creators. Competitive advantage also influences marketing performance and can mediate the relationship between market orientation and product innovation on the marketing performance of TikTok shop content creators. Suggestions for TikTok Shop content creators to implement market orientation strategies and product innovation that are appropriate to the business sector they are undertaking so that they will increase their competitive advantage which will improve marketing performance